Paternal half-sisters or unrelated – How can the X-chromosomal evidence be quantified when one female presents trisomy X?. (December 2022) - Faustino, Marisa; Turchi, Chiara; Kling, Daniel; Gusmão, Leonor; Amorim, António; Pinto, Nádia
Abstract: The X chromosome has unique features, such as haplodiploid mode of genetic transmission, which can be crucial to complement autosomal profiling or to disentangle complex kinship problems. Indeed, for some cases (e.g. full- or paternal half-sisters, or paternal grandmother-granddaughter hypotheses), X-markers are expected to provide a similar or a higher power to the one obtained with autosomes in paternity/maternity investigations. Both theoretical and informatics frameworks for pairwise X-linked kinship analyses are well established for individuals with a regular number of chromosomes, but these are still lacking for individuals exhibiting an X chromosome aneuploidy, such as females with Triple X (47, XXX) syndrome. Indeed, this work was motivated by a real forensic case involving the evaluation with X-chromosomal markers of the hypotheses that two women were related either as paternal half-sisters or as unrelated, one of them showing a trisomy X. In this case, the analysis of X-chromosomal markers would yield stronger results than autosomes, as females had to share at least one identical allele in each analyzed X chromosome marker under the paternal half-sibling hypothesis, unless a mutation occurs. To fulfill this gap, we present in this work algebraic formulae for some genotypic configurations, which will allow quantification of the evidence on the referred cases. A general approach, comprising other X chromosome aneuploidies, kinship hypotheses, and genotypic configurations, is currently being developed by us. This work is the starting point to analyze X-chromosomal data under the scope of kinship problems, involving individuals with aneuploidies. This will improve the quantification of DNA evidence not only in forensic casework, but also in the field of medical genetics, whenever individuals with X-chromosomal aneuploidies are involved.